Evaluation Of Polyoxin D Zinc Salt 5% Sc Against Powdery Mildew Of Grape (Journal of Plant Disease Sciences, 2021)
The study of the evaluation of an antifungal antibiotic Polyoxin D zinc salt 5% SC against powdery mildew of grape was conducted on grape variety Thompson seedless at Onion and Grape Research Station, Pimpalgaon Baswant, Nashik (Maharashtra). The Polyoxin D zinc salt 5% SC @ 30 g ai./ha recorded significantly lowest per cent disease index of powdery mildew on leaves and bunches (2.75 % and 2.25 %) after 15 days of first spray and (4.33 % and 2.92 %) after 15 days of second spray respectively over rest of the treatments respectively over rest of the treatments. The untreated control treatment recorded maximum per cent disease index (32.58 %, 18.75 %) on leaves and bunches, respectively. The Polyoxin D zinc salt 5% SC @ 30 g a.i./ha treatment produced a significantly maximum yield (19.52 t/ha) than the other treatments. This was followed by Polyoxin D zinc salt 5% SC @ 20 g ai./ha and hexaconazole 5% EC @ 50 g ai/ha. The untreated control treatment produced the lowest yield (13.92 t/ha) compared to the other treatments. None of the treatments of Polyoxin D zinc salt 5% SC @ 30 g a.i./ha and 60 g a.i./ha shown any type of phytotoxicity symptoms on grapes plants after 1,3,5,7 and 10 days after 1st spray.
Keywords: D zinc salt; Grape; Polyoxin and Powdery mildew